2017
DOI: 10.1016/j.bbi.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell-derived extracellular vesicles ameliorate inflammation-induced preterm brain injury

Abstract: MSC-EV treatment significantly ameliorated inflammation-induced neuronal cellular degeneration reduced microgliosis and prevented reactive astrogliosis. Short-term myelination deficits and long-term microstructural abnormalities of the white matter were restored by MSC-EV administration. Morphological effects of MSC-EV treatment resulted in improved long-lasting cognitive functions INTERPRETATION: MSC-EVs ameliorate inflammation-induced cellular damage in a rat model of preterm brain injury. MSC-EVs may serve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
191
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 234 publications
(214 citation statements)
references
References 76 publications
9
191
0
2
Order By: Relevance
“…In addition, we and others have applied MSC-EVs to an increasing amount of different animal models for various diseases. We did not detect any side effects of the MSC-EV administration in any of our animal models (79)(80)(81), even though MSC-EVs prepared with the PEG method were applied in up to 100 fold higher doses per Gramm body weight to the animals than to the respective acute GvHD patient. Furthermore, irrespectively of the protocol used for the MSC-EV purification, we are not aware of any reported side effects of the MSC-EV administration in any of the published animal models.…”
Section: Safety Of Msc-ev Administrationmentioning
confidence: 66%
“…In addition, we and others have applied MSC-EVs to an increasing amount of different animal models for various diseases. We did not detect any side effects of the MSC-EV administration in any of our animal models (79)(80)(81), even though MSC-EVs prepared with the PEG method were applied in up to 100 fold higher doses per Gramm body weight to the animals than to the respective acute GvHD patient. Furthermore, irrespectively of the protocol used for the MSC-EV purification, we are not aware of any reported side effects of the MSC-EV administration in any of the published animal models.…”
Section: Safety Of Msc-ev Administrationmentioning
confidence: 66%
“…Fluorescence microscopy and flow cytometric analyses confirmed incorporation of eGFP into the N-KM cells (Figure 5(e)), implying that purified CD63-eGFP labelled EVs still retain their properties to be taken up by N-KM cells. Using the same protocol to prepare sEVs from supernatants of MSCs, we demonstrated that these MSC-EVs were able to exert therapeutic effects in different animal models and in a human GvHD patient [14,16,52,53]. Since these PEG-prepared sEV samples exerted the same therapeutic effects in a murine ischemic stroke model than corresponding MSCs [16], our results demonstrate the usability of the PEG-precipitation method as a scalable method for the enrichment of biologically active sEVs.…”
Section: Resultsmentioning
confidence: 99%
“…In proof of principle experiments, we show that sEVs prepared with the PEG method are effectively incorporated into target cells. Furthermore, we have successfully used the optimised PEG method to prepare sEV samples for the preclinical and clinical setting from several litres of MSC-conditioned media [14,16,52,53]. Upon comparing the therapeutic impacts of such MSC-EV samples with that of corresponding MSCs in a murine ischemic stroke model, we did not detect any functional difference [16].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MSCs are capable of switching microglia from a proinflammatory M1 phenotype towards an anti-inflammatory M2 phenotype in vitro [13] and in SCI models [50]. Furthermore, MSCs inhibit reactive astrogliosis in inflammationinduced preterm brain injury [51], attenuate GFAP overexpression in astrocytes in stroke [52], and modulate astrocytic end-feet in lipopolysaccharide-treated rats [53]. However, little is known about the effect of MSCs on inflammatory A1 astrocytes after SCI.…”
Section: Discussionmentioning
confidence: 99%